1978
DOI: 10.1002/1097-0142(197807)42:1<299::aid-cncr2820420145>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation: A possible etiological factor in malignant melanoma in israel.A retrospective study (1960–1972)

Abstract: Both the incidence and mortality from malignant melanoma are rising rapidly in all countries in which they have been studied. Solar radiation has been incriminated as a possible cause for this trend and as a possible etiological factor in malignant melanoma. Israel is a subtropical country developed as a result of waves of immigration mainly in the last century from Europe, Asia, and Africa. To evaluate the role of solar radiation on the pathogenesis of malignant melanoma, 966 cases of malignant melanoma, diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…20 As expected, we found a strikingly different incidence of melanoma by origin, with low rates among the North African and Asian origin group and highest rates among those of European origin, similar to previous studies in the Israeli population. [11][12][13][14][15] In our cohort, we were able to explore for the first time the extent to which these differences were confounded or mediated by other risk factors such as birth cohort, height/BSA and socio-demographic characteristics. The strong association of origin with CM risk was only moderately attenuated after adjustment for these covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 As expected, we found a strikingly different incidence of melanoma by origin, with low rates among the North African and Asian origin group and highest rates among those of European origin, similar to previous studies in the Israeli population. [11][12][13][14][15] In our cohort, we were able to explore for the first time the extent to which these differences were confounded or mediated by other risk factors such as birth cohort, height/BSA and socio-demographic characteristics. The strong association of origin with CM risk was only moderately attenuated after adjustment for these covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Striking differences in risk of CM by origin have been noted previously in Israel. [11][12][13][14][15] This unique setting in Israel and our extensive dataset allowed us to conduct a large-scale migrant cohort study to identify high risk populations and critical periods of sun exposure during childhood, which would aid in directing public health and research efforts. Our objective was to determine the associations of origin and age at immigration with the risk of CM and examine the extent to which these associations are explained by other risk factors such as birth cohort and socio-demographic and anthropometric characteristics.…”
mentioning
confidence: 99%
“…Previous studies of migrants to Israel, for shorter periods, have suggested similar results (Anaise et al, 1978;Katz et al, 1982). Similar findings have been noted for European migrants to Australia, who have lower incidence rates than the Australia-born population, but an increasing risk with longer duration of residence (Dobson and Leeder, 1982).…”
Section: Malignant Melanomamentioning
confidence: 99%
“…Malignant melanoma incidence and mortality in whites are related to latitude of residence (Lancaster, 1956;Elwood et al, 1974;Magnus, 1976), duration of residence in a sunny place (Movshovitz & Modan, 1973;Anaise et al, 1978) and ability to tan. The tumours select exposed anatomical sites, with particular reference to the different clothing and hair styles of men and women (Elwood & Lee, 1975;Committee, 1976).…”
mentioning
confidence: 99%